Estimating Tourist Growth at Destination Sites: A Mathematical Equation and a Connectivity Model Through Mobile Application (Baghdad Science Journal, 2024)
Social science researchers have endeavored with the literature showcasing various individual mobile recommendation systems to assist stakeholders in the tourism sector. The challenge of formulating a mathematical equation to predict tourist growth at specific sites arises due to the diverse environmental conditions unique to each destination. This research seeks to develop a mobile application model fostering connectivity among significant tourism stakeholders. Within the app, stakeholders can effortlessly retrieve information about others and directly engage with relevant authorities without exiting the application. The app also provides navigation guidance to tourist destinations. The study explores the specific growth rate of tourists, assuming a doubling of tourist numbers after a specific time interval has been illustrated. While there may be an initial exponential growth in tourist numbers at a destination, the count eventually stabilizes. The Monod equation is employed in conjunction with the tourist equation for a comprehensive representation in this study. Additionally, the research delves into the graphical analysis of the feasibility conditions proposed by Casagrandi and Rinaldi's connectivity model. It is essential to note that this analysis remains abstract, and the creation of a universally applicable mathematical tourism model for every destination proves nearly impossible.